Biomass accumulation in an ornamental Cactaceae (Mammillaria elongata subsp. echinaria) in response to a single 6-benzylaminopurine (BAP) spray - Lozano Miglioli, Jorge (2019)
Fil: Lozano Miglioli, Jorge. Scientific Research Committee of the Province of Buenos Aires (CIC). La Plata, Buenos Aires, Argentina.